Efforts to Improve School Effectiveness in Organizations - Ardianti Ardianti (Indonesian Journal of Education (INJOE), 2022)
The concept of an effective school is the specification of the organizational development process in the principal's management process that is in accordance with the actual needs of the school. This managerial efficiency is characterized by the optimal functioning of the organizational structure, teacher and professional performance, progressive student preparation and learning. School effectiveness is also reflected in the implementation and development of academic activities and the achievement of educational goals. Therefore, the more skilled school principals, teachers, and school staff are in carrying out their duties and responsibilities, the more efficient and effective the entire school system and services will be